Artificial intelligence of optimal real power dispatch with constraints of lines overloading - Abdesselam Abderrahmani; Nasri Abdelfatah; Gasbaoui Brahim (Institute of Advanced Engineering and Science, 2023)
In the literature on optimal power flow (OPF), it has been shown that the suggested ways offer a higher degree of satisfaction in optimizing overall production costs while fulfilling power flow equations, system security, and equipment operational constraints. Despite this, the overloaded of the transmission lines are taken as a performance index but not a primary constraint. This article presents an improved approach to artificial intelligence algorithms of optimal real power dispatch with the security of lines; the main difference concerning our point seen relies on the additional penalization of the choices, which does not respect this constraint. The problem is implemented in the IEEE 14-bus system with